Mapping Central Projection of Oxytocin Neurons in Unmated Mice Using Cre and Alkaline Phosphatase Reporter - Liao, Po-Yu; Chiu, Yan-Min; Yu, Jo-Hsien; Chen, Shih-Kuo (Frontiers in Neuroanatomy, 2020)
Oxytocin, a neuropeptide and peptide hormone, is produced by neurons in the hypothalamus and released by the posterior pituitary to control breastfeeding and labor. Recent studies have revealed that oxytocin in the central nervous system is also involved in modulating social interaction. To understand the potential role and innervation pattern of oxytocin neurons before sexual interaction, here we used transgenic mice which has the Cre recombinase under the control of an endogenous oxytocin promoter and Cre dependent human placental alkaline phosphatase (hPAP) reporter to label the oxytocin neurons in the naive mouse brain. Since AP is located on the membrane of oxytocin neurons, the AP histochemistry staining enabled us to observe the fine axonal terminals and the innervation pattern of oxytocin neurons in the thick serial coronal brain slices. Here we show that the number of AP labeled cells vary with staining reaction time and range from 30% of the oxytocin immune-positive cell count to slightly higher than the oxytocin immune-positive cell count. Using AP staining with extended reaction time, which may not label all oxytocin neurons, we confirmed many innervation targets of oxytocin neurons from the anterior olfactory nucleus, some cortex regions, the limbic system, the hypothalamus, and the hindbrain, while the cell bodies were exclusively located in the hypothalamus and the bed nucleus of the stria terminalis (BST). Finally, we observe some individual variance at the olfactory area, isocortex, striatum, Paraventricular nucleus of thalamus, Locus coeruleus, and Barrington’s nucleus.